2017
DOI: 10.1002/chem.201703627
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Observation and Molecular Dynamics Simulation of Ga Surface Segregation in Liquid Pd–Ga Alloys

Abstract: Liquid binary Pd-Ga alloys with low Pd contents of 0.8, 1.8, and 4.7 at % of Pd were examined as a function of sample temperature in ultra-high vacuum by using angle-resolved XPS. Upon cooling from 750 to 400 K, a pronounced temperature-dependence of the Pd concentration in the liquid phase was observed, which was explained by the transition from the pure liquid phase to a two-phase system, consisting of a solid Ga Pd phase and a Pd-depleted liquid Pd-Ga alloy. In the liquid Pd-Ga alloy, Pd is always depleted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“… 1 , 3 In short, the outer layer of the liquid alloy droplets is typically depleted in atoms of the catalytically active metal. 10 In the presence of the reactants, however, the catalytically active metal atoms appear as single atoms at the gas–liquid metal interface to provide their catalytic reactivity to the system. Upon desorption of the formed products, the active metal atoms dive back into the bulk of the Ga-rich droplets resulting in a self-regenerating process of the catalytically active interface.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 3 In short, the outer layer of the liquid alloy droplets is typically depleted in atoms of the catalytically active metal. 10 In the presence of the reactants, however, the catalytically active metal atoms appear as single atoms at the gas–liquid metal interface to provide their catalytic reactivity to the system. Upon desorption of the formed products, the active metal atoms dive back into the bulk of the Ga-rich droplets resulting in a self-regenerating process of the catalytically active interface.…”
Section: Introductionmentioning
confidence: 99%
“…Ga. [10][11][12]19 The catalytic reaction in SCALMS occurs exclusively at the liquid metal/gas interface. 10,12,[19][20][21][22][23][24][25] Contrary to conventional SLP catalysis, the reactants and products are insoluble in the liquid phase. In addition, the liquid metal/gas interface is highly dynamic on an atomic scale.…”
Section: Introductionmentioning
confidence: 99%
“…The topmost layer of the Ga-rich alloy droplets is depleted of active metal atoms in the absence of substrates. 10,12,20,21 Nevertheless, the active metal atoms may diffuse to the surface of the droplets and interact with substrates via adsorption, which is a prerequisite for the catalytic activity of SCALMS. In the case of PDH over Ga-Rh SCALMS, ab initio molecular dynamics simulations suggest that the presence of a propane molecule at the liquid metal/gas interface may trigger the diffusion of Rh atoms to the surface of the liquid alloy droplet.…”
Section: Introductionmentioning
confidence: 99%
“…: Ga 21 Rh 4 , Ga 16 Rh 3 in Rh-Ga model SCALMS particles). [1][2][3][4][5] Temperature-dependent xray photoelectron spectroscopy (XPS) revealed that for macroscopic alloy droplets the crystallization of the intermetallic compounds (IMCs) occurs inside the bulk of the droplets, resulting in a transition-metal-depleted surface and near-surface region. Upon heating above the liquidus temperature, the IMCs dissolve in the liquid Ga phase, yielding a fully liquid alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Upon heating above the liquidus temperature, the IMCs dissolve in the liquid Ga phase, yielding a fully liquid alloy. [3][4][5] Abinitio molecular dynamics (AIMD) simulations showed that the near-surface region of liquid Pd-Ga, Pt-Ga, and Rh-Ga SCALMS systems has a layered structure along the surface normal: The first atomic layer is transition-metal-depleted, and the second layer is transition-metal-enriched with the expected bulk density approached over the next few layers. These results have been confirmed by angle-dependent XPS for the Pd-Ga system.…”
Section: Introductionmentioning
confidence: 99%